Evaluating surface protonic transport on cerium oxide via electrochemical impedance spectroscopy measurement. (February 2018) - Manabe, Ryo; Stub, Sindre Østby; Norby, Truls; Sekine, Yasushi
Abstract: Surface protonic transport on cerium oxide (CeO2 ) was investigated using electrochemical impedance spectroscopy (EIS). CeO2 pellets showing low relative density: approximately 60%, was prepared for the purpose. The structure and morphology of the prepared CeO2 pellets were confirmed from XRD and SEM measurements. Results show that the pellets had a pure cubic phase, with open pores on which water can be adsorbed. Electrochemical impedance spectroscopy measurements were taken to evaluate the surface protonic transport on CeO2 as a function of temperature and as a function of partial pressure of water ( P H2O ) at 400 °C. Investigations of the temperature dependence of the conductivity revealed that only the conductivities of surface grain bulk ( σ intra ) and surface grain boundary ( σ inter ) increased with decreasing temperatures under wet conditions ( P H2O  = 0.026 atm). The P H2O dependence of surface conductivities ( σ intra and σ inter ) revealed that σ intra increases strongly with P H2O at 400 °C. These findings provide evidence that water adsorbates play an important role in surface protonic transport on CeO2 at low temperatures. Surface protonic transport at low temperatures can contribute to the expansion of applications for electrical and catalytic processes. Highlights: Surface protonic transport on CeO2 was investigated using electrical impedance spectroscopy. CeO2 pellets showing low relative density: approximately 60%, was used. The conductivities of surface grain bulk increases with P H2O at 400 °C. The conductivities for surface increased with decreasing temperatures under wet conditions.